ON THE POSSIBILITIES OF ATTENUATION OF ANTIPLATELET THERAPY INTENSITY IN PATIENTS AFTER ACUTE CORONARY SYNDROME. RESOLUTION OF THE PANEL OF EXPERTS OF THE EMERGENCY CARDIOLOGY SOCIETY - Article Editorial («REMEDIUM GROUP» Ltd., 2018)
.